Impact of Speech Therapy on Communication Skills and Social Interaction in Children with Autism Spectrum Disorder - Venita, Yura; Devina, Arnyta (International Journal of Nursing and Midwifery Research, 2024)
This research investigates the impact of speech therapy on children diagnosed with autism spectrum disorder (ASD), focusing on improvements in communication skills, social interactions, and overall development. Utilizing a mixed-methods approach, the study integrates quantitative assessments and qualitative insights to comprehensively evaluate the efficacy of speech therapy interventions over a 6-month period. Quantitative measures include standardized assessments of language proficiency, social skills, and adaptive behaviors administered pre- and post-intervention. Qualitative data are gathered through interviews with parents/caregivers and observations of therapy sessions to capture subjective experiences and perceptions. Findings reveal significant advancements in communication abilities, evidenced by enhanced language acquisition, improved articulation, and increased comprehension skills. Participants also demonstrate improved social interactions, such as initiating conversations, interpreting social cues, and engaging in peer activities. Overall developmental gains include heightened self-confidence, reduced behavioral challenges, and enhanced adaptive skills crucial for daily functioning. Implications highlight the role of speech therapy in supporting children with ASD and their families, advocating for inclusive educational practices and equitable access to therapeutic services. Recommendations for future research emphasize optimizing intervention strategies, conducting longitudinal studies, and promoting collaborative efforts across healthcare, educational, and policy domains.